Detailed Structural Typology of Existing Substandard Masonry and Reinforced Concrete Buildings in the City of Zagreb, Croatia - Marta Šavor Novak; Mario Uroš; Marija Demšić; Romano Jevtić Rundek; Ante Pilipović; Josip Atalić (Buildings)
Despite significant scientific and technological advancements in earthquake engineering, earthquakes continue to cause widespread destruction of the built environment, often resulting in numerous fatalities and substantial economic losses. Southeastern Europe, which includes Croatia, is part of the Mediterranean–Trans-Asian high-seismic activity zone. This area has recently experienced a series of earthquakes which had severe consequences for both populations and economies. Notably, the types of buildings that suffered significant damage or collapse during these events still constitute a large portion of the building stock across the region. The majority of residential buildings in Croatia and neighboring areas was constructed before the adoption of modern seismic standards, indicating that a considerable part of the building stock remains highly vulnerable to earthquakes. Therefore, the main goal of this study is to identify the building types which significantly contribute to seismic risk, with the focus on Zagreb as Croatia’s largest city and the capital; collect the documentation on the structural systems and occupancy; analyze the data; and carry out the initial vulnerability assessment. This serves as a first step toward developing a new exposure and vulnerability model for Zagreb that is also applicable to all urban areas in the region with similar building stock and seismotectonic conditions.